Modelling and Forecasting Business Cycle in CEE Countries using a Threshold Approach - Osińska, Magdalena; Kufel, Tadeusz; Błażejowski, Marcin; Kufel, Paweł (Dynamic Econometric Models, 2016)
We propose to apply a time-series-based nonlinear mechanism in the threshold autoregression (TAR) form in order to examine business cycles in Central and Eastern European economies and compare them to the entire EU business cycle. The threshold variables, such as consumer price index, short and long interest rates, unemployment rate and an exchange rate vs. the U.S. Dollar, have been considered. The purpose of the paper is to model and to predict business cycles in Central and East European (CEE) economies (the EU Member States) and compare them to business cycles of the entire EU28 area and Eurozone EU19. We found that the exogenous mechanism played an important role in diagnosing the phases of business cycles in CEE economies, which is in line with the entire EU economic area. The results of business cycle forecasting using bootstrap technique are quite promising, while bootstrap confidence intervals are used for diagnosis.